Psychometric reproducibility properties analysis of the Oral Health Impact Profile (OHIP-49) in patients with periodontal disease (Revista Nacional de Odontología, 2019)
Introduction: the oral health related quality of life measurement is considered a daily life negative effect indicator due to patients’ oral condition. The Oral Health Impact Profile (OHIP-49) is an extended-use instrument, the readers should to expect the researchers to present the psychometric properties analysis, which describe the instrument behavior in the study population. The purpose is to evaluate the OHIP-49 reproducibility properties when is applied in patients with periodontal disease, who attend two dental healthcare institutions.Methods: we included 207 participants how it is suggested from the International Test Commission for similar purposes. We included 91 men and 116 women for convenience; reproducibility properties were evaluated: reliability, internal consistency, item discriminant validity, and content validity.Results: Cronbach’s alpha of 0.951 was obtained and high success percentages for internal consistency (87.5%-100%); the item discriminant validity not achieved acceptable success percentages (16,6% -68,5%). We decided to review the instrument content structure, with which a seven-factor model was obtained. According to the clinical situation, when we compared them with the less severe cases, patients with periodontitis stage III and IV presented worst quality of life represented in the dimensions of functional limitation, chewing, swallowing and aesthetics.Conclusions: a good instrument performance was obtained for this Colombian Caribbean Coast population; but it is valid to consider reducing dimensions to improve reproducibility scores.
Keywords: validation studies; quality of life; periodontitis; epidemiology; statistics